2019
DOI: 10.3748/wjg.v25.i35.5266
|View full text |Cite
|
Sign up to set email alerts
|

Significance of tumor-infiltrating immunocytes for predicting prognosis of hepatitis B virus-related hepatocellular carcinoma

Abstract: BACKGROUNDHepatitis B virus (HBV) has been recognized as a leading cause of hepatocellular carcinoma (HCC). Numerous reports suggest that immune infiltration can predict the prognosis of HCC. Nonetheless, no creditable markers for prognosis of HBV-related HCC have been established by systematically assessing the immune-related markers based on tumor transcriptomes.AIMTo establish an immune-related marker based on the cell compositions of immune infiltrate obtained based on tumor transcriptomes, so as to enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 28 publications
(27 reference statements)
0
18
0
Order By: Relevance
“…Thus, although patients with a high degree of immune cell infiltration may have a high IRS, the IRS based on the five immune associated genes primarily accounted for the functional status of the microenvironment in HCC tissues. Recent studies have focused on the roles of infiltrating immune cells in the tumor microenvironment, to explain the mechanisms underlying immune evasion and to predict drug response or prognosis (75)(76)(77). Further analysis of the sub-types of immune cells in HCC may improve our understanding of immune function in tumor, and with advances in technologies, changing the types of immune cells present may be considered as a potential treatment strategy, emphasizing the importance of restoring immune function in HCC (78)(79)(80).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, although patients with a high degree of immune cell infiltration may have a high IRS, the IRS based on the five immune associated genes primarily accounted for the functional status of the microenvironment in HCC tissues. Recent studies have focused on the roles of infiltrating immune cells in the tumor microenvironment, to explain the mechanisms underlying immune evasion and to predict drug response or prognosis (75)(76)(77). Further analysis of the sub-types of immune cells in HCC may improve our understanding of immune function in tumor, and with advances in technologies, changing the types of immune cells present may be considered as a potential treatment strategy, emphasizing the importance of restoring immune function in HCC (78)(79)(80).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the thirteen m 6 A RNA methylation regulators were screened and verified by least absolute shrinkage and selection operator (LASSO) regression using the 'glmnet' R software. Finally, the regulator-based prognostic risk score was constructed through linearly multiplying the expression level with the regression model (β) according to the following formula: Risk=β regulator 1 x regulator 1 expression + β regulator 2 x regulator 2 expression + • •••• + β regulator n x regulator n expression (15,16).…”
Section: Methodsmentioning
confidence: 99%
“…These results similarly con rm the dependability of the risk model. Previous reports have shown that immune in ltration is a vital factor affecting the e cacy as well as the prognosis of HCC [22,23]. Ma et al [24] reported that PD1 Hi CD8 + T cells correlated with poor clinical outcome in HCC.…”
Section: Discussionmentioning
confidence: 98%